The Quaternion identity expresses the product of any two numbers, each expressed as the sum of four squares, as the sum of four squares.

(a2+b2+c2+d2)(A2+B2+C2+D2) = (aA+bB+cC+dD)2+(aB-bA-cD+dC)2+(aC+bD-cA-dB)2+(aD-bC+cB-dA)2

Derivation from quaternionsEdit

The quaternion units 1,i,j,k are defined so that

1 = 1*1 = -i2 = -j2 = -k2
i = 1i = i1 = jk = -kj
j = 1j = -ik = j1 = ki
k = 1k = ij = -ji = k1

If u=a-bi-cj-dk, U=A+Bi+Cj+Dk, then from


we get

(a2+b2+c2+d2)(A2+B2+C2+D2) = (aA+bB+cC+dD)2+(aB-bA-cD+dC)2+(aC+bD-cA-dB)2+(aD-bC+cB-dA)2

In defining u, the signs of b, c, and d are arbitrary; We could have just as easily defined them differently (or permuted the meanings of A, B, C and D). The important observations to make regarding the sign of the variables a,b,c,d,A,B,C,D on the right hand side of the equation are:

  • One of the eight variables, which we will arbitrarily call a has a positive sign whereever it appears. This fixes a as one of the lower-case variables.
  • One of the four variables upper-case variables, which we arbitrarily call A has a negative sign wherever it appears, except with a. This fixes the relationship between a and A.
  • Then the pairing of b, c, and d with B, C, and D is such that bC, cD, and dB have a negative sign; and cB, dC, and bD have a positive sign.


By defining u=a-bi-\sqrt{n}cj-\sqrt{n}dk\, and U=A+Bi+\sqrt{n}Cj+\sqrt{n}Dk\,, then from


we get

(a2+b2+nc2+nd2)(A2+B2+nC2+nD2) =


A simple application of this identity is

3(A^2+B^2+C^2+D^2) = (A+B+C)^2+(D+A-B)^2+(C+D-A)^2+(B-C+D)^2

See alsoEdit

  • Complex product identity, that the product of two numbers expressed as the sum of two squares can be expressed as the sum of two squares.

Ad blocker interference detected!

Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.